Emotive responses to ethical challenges in caring: A Malawian perspective - Msiska, Gladys (Nursing ethics, 2014)
This article reports findings of a hermeneutic phenomenological study that explored the clinical learning experience for Malawian undergraduate student nurses. The study revealed issues that touch on both nursing education and practice, but the article mainly reports the practice issues. The findings reveal the emotions that healthcare workers in Malawi encounter as a consequence of practising in resource-poor settings. Furthermore, there is severe nursing shortage in most clinical settings in Malawi, and this adversely affects the performance of nurses because of the excess workload it imposes on them. The results of the study also illustrate loss of professional pride among some of the nurses, and the article argues that such a demeanour is a consequence of burnout. However, despite these problems, the study also reveals that there are some nurses who have maintained their passion to care.